Предмет: Алгебра, автор: nastya0gorban

(a^2-1)(a+a^2+a^3)/(a^4-a)упростить

Ответы

Автор ответа: konrad509
0

\frac{(a^2-1)(a+a^2+a^3)}{(a^4-a)}=\ frac{(a-1)(a+1)a(a^2+a+1)}{a(a^3-1)}=\ frac{(a-1)(a+1)(a^2+a+1)}{(a-1)(a^2+a+1)}=\ a+1

Автор ответа: Svet1ana
0

frac{(a^{2}-1)(a+a^{2}+a^{3})}{(a^{4}-a)}=frac{(a^{2}-1)(a^{3}+a^{2}+a)}{(a^{4}-a)}= frac{(a^{2}-1)(a(a^{2}+a+1))}{a(a^{3}-1)}=frac{(a+1)(a-1)(a^{2}+a+1)}{(a^{3}-1)}=

frac{(a+1)(a-1)(a^{2}+a+1)}{(a-1)(a^{2}+a+1)}=a+1

Похожие вопросы
Предмет: Другие предметы, автор: onlinenekteo
Предмет: Алгебра, автор: emka